Potential of the region of creation Ocaña a tourist cluster - Pacheco Carrascal, Marilce; Navarro Claro, Genny Torcoroma (Universidad Francisco de Paula Santander, 2015)
The city of Ocaña, along with the municipalities of La Playa, Ábrego and El Carmen, located in the department of Norte de Santander, Colombia, possess great cultural, historical and natural wealth, which allow projecting this region as a tourist destination, but nowadays the culture that prevails around economic activities focuses on trade; tourism is an activity that entrepreneurs do not see clearly and only a few of tem have opted to develop projects in this area. After an inventory, it was found that there are enough attractions, but the business system must be organized so that the tourism sector can be empowered and to develop activities in a sustainable and responsible manner; For this reason, entities such as the Chamber of Commerce of Ocaña, The Francisco de Paula Santander Ocaña University, SENA, the City Hall, the private enterprise and other local and national institutions must design projects that favor the improvement of the business network that in an efficient and competitive way they point to the development of this sector. The idea is to propose associative and complementary strategies so that tourism can be offered with quality in a sustainable, responsible and participative way, generating a true economic development.